Fencing effects on mountain ranges of the Sierra del Segura - Selva Denia, M.; Orozco Bayo, E.; Martínez Sánchez, J. J.; López Donate, J. A. (Forest Systems, 1999)
Fencing influence on overgrazed ranges of the Sierra del Segura is studied, over two fenced plots, during three years. An important increment of cover in herbaceous plants of elevated pastoral value, mainly perennial legumes, is observated. Uncovered soil ratio decreased by effect of fencing. Woody species of elevated pastoral value increment their cover. An important increment in floral richness and diversity is produced during the first year after fencing. Appearance species ratio decreased after the first year.